Nilai Moral dalam Novel Bukan Salah Hujan Karya Ummuchan - Purnami, Pramesty Dewandini; Sudewa, I Ketu; Banda, Maria Matildis (Suara Bahasa, 2024)
The moral decline of Indonesian teenagers is a critical problem that must be faced and a solution must be found so that morality, which is the nation's identity, can remain. The role of Indonesian youth for the country's progress in the future is very important. If their souls do not have morality, then the state cannot have good and responsible leaders. The existence of literary works is a medium for authors to convey values such as moral values. Literary works can be a weapon to instill character education in their readers. One of the literary works in the form of a novel entitled Bukan Salah Hujan by Ummuchan contains moral values that can be considered. Therefore, the purpose of this research is to describe the morality contained in the novel Bukan Salah Hujan (BSH) by Ummuchan using moral analysis according to Burhan Nurgiyantoro. This type of research is qualitative and the method used is descriptive. The source of data for this research is the novel Bukan Salah Hujan (BSH) by Ummuchan which totals 226 pages. The data analysis method used is descriptive analytics and the techniques are reading, listening, taking notes, and interpretation. The results of the research obtained consist of three forms of moral values, namely: (1) human relationships with themself, including self-confidence, patience, admitting mistakes, and hard work; (2) human relationships with other human beings, including affection, help, and reciprocity; and (3) human relationship with God, including grateful.